Development of means of combating armored vehicles at the forefront of defense. The first half of the 1930s. Based on the materials of the Soviet military press - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
In the article on the materials of the military press of the first half of the 1930s. the author analyzes the change in views on the fight against armored vehicles in the specified period. The author considers the main addition and alternatives to anti-tank guns, which were popular with military theorists considering the issues of countering armored vehicles at a distance of up to a kilometer. In the course of his work, the author considers proposals on the tactical and technical aspects of using various types of grenades against armored vehicles, mines, bi-calibre artillery system, heavy machine guns, automatic guns received from both foreign and domestic experts. As a result of the study, the author comes to the conclusion that in the USSR in the first half of the 1930s. the military leadership quickly came to the conclusion that anti-tank guns were needed to fight tanks, and grenades and mines could play a very limited role in the fight against armored vehicles. While outside the USSR, heavy machine guns, automatic guns, field artillery guns continued to be considered as anti-tank weapons. Thus, we can say that in the USSR the conceptual awareness of the vector of counteraction to armored vehicles occurred earlier than in Germany, France, the British Empire, the United States of America and Poland.